The Curriculum - A Major Key Issues for Student Satisfaction - Adriana Daniela Şerban (University Babes-Bolyai, 2018)
Student satisfaction, the students' choice of a higher education institution as well as the link between these aspects and the efforts of universities to ensure high retention rates have been an important topic of research in the last ten years. The quality of instruction and its effectiveness are issues prior to student satisfaction; however, their expectations are more wider-ranging. This paper aims to present the results of an analysis regarding the satisfaction levels of students enrolled in bachelor and master degrees at Babeș-Bolyai University from Cluj-Napoca, Romania The article focuses on the issues that the students find to be the least satisfactory and which, as a result, could be important aspects for their satisfaction. The results show that, besides the academics' teaching performance, the curriculum, the possibility of choosing the study subjects and the practical skills acquired are major key issues.